Strategic leadership and financial governance in liver transplantation: global insights from the International Liver Transplantation Society Congress 2025 - Putri, Aghnia Jolanda; Czigány, Zoltán; Kow, Alfred W. C.; Maluf, Daniel G.; Selzner, Markus (Liver transplantation, 2025)
The 2025 International Liver Transplantation Society (ILTS) Congress, held in Singapore, brought together a global, multidisciplinary community to explore innovations and persistent challenges in liver transplantation (LT). The congress included seven pre-congress workshops, 92 scientific sessions, and featured 270 expert speakers. More than 1100 participants from 71 countries took part in the event. A new focus was the growing importance of strategic leadership and financial governance in sustaining and expanding liver transplant programs. A series of presentations, symposiums, and workshops focused on leadership and financial governance brought together clinical and administrative leaders to explore the operational frameworks and economic strategies critical to the long-term sustainability of liver transplant programs. Discussions emphasized the need for robust reimbursement models, clear cost-effectiveness frameworks, and integration of emerging technologies into diverse healthcare systems.